Bidirectional Peptide Translocation through Ultrasmall Solid-State Nanopores - Wei, Guanghao (Langmuir : the ACS journal of surfaces and colloids, 2024)
It is important to obtain the configuration of polypeptides and the sequence information on amino acids for understanding various life processes and many biological applications. Nanopores, as a newly developed single-molecule detection technology, exhibit unique advantages in real-time dynamics detection. Here, we designed a special peptide chain with 10 arginine in the head and achieved successful single-molecule detection by ultrasmall solid-state nanopores (2-3 nm). Unique bidirectional translocation signals were observed and explained under the framework of charge distribution of the peptide and interaction with the nanopore wall. Two natural peptide chains, histatin-5 and angiopep-2, were also explored by nanopore experiments to confirm our conjecture. Our designed peptide chain could realize multiple detections of the same peptide chain, offering possibilities for high-resolution peptide detection and fingerprinting by solid-state nanopores in the future